The State of Relief on the Bangladesh-India Border - Delwar Hussain (South Asia Multidisciplinary Academic Journal)
By focusing on a remote part of the Bangladesh-India border, this paper seeks to understand how the state has been reconfigured from its older, developmental paradigm, involving large-scale infrastructural change and resource redistribution, to its contemporary NGO-driven avatar. The paper suggests that the state today is merely one of multiple governing agencies that participate in producing ‘state-like effects’ on a territory and its population. Sometimes these agencies are in competition; often they work alongside one another. NGOs are agencies of this kind and are a major focus of this paper. In light of this, the idea of a sovereign Bangladeshi state which is apparently being eroded by neoliberalism, is not a complete picture. Other than a particular moment in the post-colonial period where there was optimism that the contrary would be achieved, sovereignty has in fact always been a mediated, fragmented affair in the borderlands as well as in Bangladesh as a whole.